Activation of Mo2B Catalyst in the Epoxidation Reaction of α-Ethylallyl Ethyl Acrylate with tert-Butyl Hydroperoxide - Komarenska, Zoryana; Oliynyk, Lilianna; Makota, Oksana (Видавництво Львівської політехніки, 2023)
Вивчено закономірності активування каталізатора Мо2В у реакції епоксидування α етилалілетилакрилату трет-бутилгідропероксидом. Показано, що процес активування каталізатора описується топохімічним рівнянням Аврамі-Єрофеєва і містить дві послідовні стадії – зародкоутворення і формування нової фази, активної в реакції епоксидування. Утворення епоксиду відбувається тільки в присутності активованої форми каталізатора. Обчислено ефективні й топохімічні константи процесу.

The regularities of Mo2B catalyst activation in the epoxidation reaction of alfa-ethylallyl ethyl acrylate with tert-butyl hydroperoxide have been studied. It has been shown that the catalyst activation process is described by the Avrami-Erofeev topokinetic equation and includes two successive stages – the nucleation and formation of a new phase active in the epoxidation reaction. The formation of epoxy only occurs in the presence of the activated form of the catalyst. The effective and topochemical process constants have been calculated.
Активування каталізатора Мо2В в реакції епоксидування α-етилалілетилакрилату трет-бутилгідропероксидом
Keywords: окиснення; кінетичні закономірності; каталізатор; олефін; oxidation; kinetic laws; catalyst olefin